Optimal control of an invasive species using a reaction‐diffusion model and linear programming. Issue 10 (24th October 2017) - Bonneau, Mathieu; Johnson, Fred A.; Smith, Brian J.; Romagosa, Christina M.; Martin, Julien; Mazzotti, Frank J.
Abstract: Managing an invasive species is particularly challenging as little is generally known about the species' biological characteristics in its new habitat. In practice, removal of individuals often starts before the species is studied to provide the information that will later improve control. Therefore, the locations and the amount of control have to be determined in the face of great uncertainty about the species characteristics and with a limited amount of resources. We propose framing spatial control as a linear programming optimization problem. This formulation, paired with a discrete reaction‐diffusion model, permits calculation of an optimal control strategy that minimizes the remaining number of invaders for a fixed cost or that minimizes the control cost for containment or protecting specific areas from invasion. We propose computing the optimal strategy for a range of possible model parameters, representing current uncertainty on the possible invasion scenarios. Then, a best strategy can be identified depending on the risk attitude of the decision‐maker. We use this framework to study the spatial control of the Argentine black and white tegus ( Salvator merianae ) in South Florida. There is uncertainty about tegu demography and we considered several combinations of model parameters, exhibiting various dynamics of invasion. For a fixed one‐year budget, we show that the risk‐averse strategy, which optimizes the worst‐case scenario of tegus' dynamics, and the risk‐neutral strategy, which optimizes the expected scenario, both concentrated control close to the point of introduction. A risk‐seeking strategy, which optimizes the best‐case scenario, focuses more on models where eradication of the species in a cell is possible and consists of spreading control as much as possible. For the establishment of a containment area, assuming an exponential growth we show that with current control methods it might not be possible to implement such a strategy for some of the models that we considered. Including different possible models allows an examination of how the strategy is expected to perform in different scenarios. Then, a strategy that accounts for the risk attitude of the decision‐maker can be designed.